Феномен дезінформації в умовах російської агресії - Михайленко, Роман Володимирович (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Direct information attacks are characterized by distortion of information without significant change in its content, and misinformation is an integral part of the hybrid war. It find new determinants of the phenomenon of existence of the transformed forms, and deepening the theoretical understanding of the methodology of the transformed forms in view of the prospects of discovering their heuristic potential. In the framework of ontological projection author reveals of the transformed forms through modern forms of social practice.